Social Media to Foster Self-organized Participatory Learning for Disengaged Learners - de Vries, Pieter (International Journal of Advanced Corporate Learning (iJAC), 2013)
The reAct project described in this paper is an innovative learning approach developed and used to re-motivate the disengaged from education and learning to connect to lifelong learning practices. These youngsters constitute a considerable social problem in Europe and the aim of the project is to find ways to recover the intrinsic motivation to learn and thereby improve the opportunities for participation. Key in this innovative strategy is self-organized learning, the learner in control of the learning process. The paper starts with an introduction on the challenge these dropouts pose to the society at large and the learning strategy developed to cope with this matter. The usage of media in the methodology is crucial and links to the concept of a user-configurable Personal Learning Environment (PLE). The main research issues are: can reAct change the attitude, what are the benefits and drawbacks of this self-organized learning approach and do the ICT tools support these processes. This paper covers the first half of the project and reflects on the first rather positive experiences.